Bioanalysis of selinexor in mouse plasma micro-samples utilizing UPLC-MS/MS - Sauter, Max; Foerster, Kathrin; Benzel, Julia; Pfister, Stefan; Pajtler, Kristian Wilfried; Haefeli, Walter E.; Burhenne, Jürgen (Journal of chromatography, 2021)
Selinexor, a first-in-class inhibitor of the nuclear export protein Exportin-1 (XPO1), was recently approved for the treatment of multiple myeloma in combination with dexamethasone, and as monotherapy for diffuse large B-cell lymphoma. To enable investigations of selinexor in mice, we established and validated an ultrahigh-performance liquid chromatography - tandem mass spectrometry (UPLC-MS/MS) assay in the plasma concentration range of 1-1000 ng/mL using plasma microsamples of 5 µL. Protein depletion with acetonitrile was used for efficient isolation of selinexor which was followed by a dilution step, resulting in a scalable sample processing. Quantification was performed with positive electrospray ionization tandem mass spectrometry in the selected reaction monitoring mode. Due to the high sensitivity of the quantification and the scalable sample processing procedure, the assay can be used for different concentration ranges to either further decrease the achievable lower limit of quantification or to reduce the amount of plasma used. The assay showed interday and intraday accuracy of 89.0-109.0% with a corresponding precision ≤ 14.1%. Suitability for investigations of selinexor in small animal experiments was demonstrated by determination of plasma selinexor in mice after oral administration.
Gesehen am 29.07.2021